The economic benefit of time‐varying surveillance effort for invasive species management. Issue 3 (29th February 2016) - Holden, Matthew H.; Nyrop, Jan P.; Ellner, Stephen P.
Summary: Government agencies develop invasive species management programmes assuming early detection is key to successful management. Some theoretical studies confirm this intuition, while others, which restrict sampling effort to be constant in time, suggest managers are investing too heavily in sampling to detect new local invader populations. We explore whether these optimal constant‐effort strategies underplay the importance of early surveillance and determine how much changing sampling effort through time reduces total management costs. Using optimal control theory to calculate time‐dependent surveillance policies that minimize the total cost of sampling, eradication, and damage by the invasive, we find that the best strategies often use intense early sampling, followed by reduced sampling effort. Intense early sampling can drastically reduce costs compared with constant‐effort strategies if propagule pressure from outside the managed area is low. However, if new infestations arise from frequent independent introductions from an outside source, constant strategies are cost‐effective. Synthesis and applications . For invasive species that are initially present, not frequently reintroduced into the managed area, and for which surveillance is reasonably cost‐effective, we recommend a simple three‐phase management programme that deploys intense early surveillance until the majority of undetected populations have been discovered, followed by medium effort until most of the heavily infested areas have been cleared of the invader and finally low long‐term effort to prevent infestations caused by future introductions and spread from populations that escaped surveillance. This programme captures the majority of the economic benefits from varying sampling effort continuously through time. Abstract : For invasive species that are initially present, not frequently reintroduced into the managed area, and for which surveillance is reasonably cost‐effective, we recommend a simple three‐phase management programme that deploys intense early surveillance until the majority of undetected populations have been discovered, followed by medium effort until most of the heavily infested areas have been cleared of the invader and finally low long‐term effort to prevent infestations caused by future introductions and spread from populations that escaped surveillance. This programme captures the majority of the economic benefits from varying sampling effort continuously through time.